Ethical Leadership and Its Role in Reducing Organizational Conflict A survey study of a sample of heads of academic departments at the University of Basrah colleges - Habeeb, Doaa (The Gulf Economist, 2025)
The research aims to examine the impact of ethical leadership on reducing organizational conflict within the colleges of the University of Basrah. The study employed a descriptive-analytical approach and used a questionnaire to collect data from 114 department heads across 22 colleges. Data were analyzed using SPSS (Version 27) and SmartPLS 4.0. The results revealed a statistically significant effect of ethical leadership practices in reducing organizational conflict and improving the university work environment. The researcher recommended implementing continuous training programs and workshops for department heads, along with adopting strategies and policies that promote transparency and fairness among the academic staff.